2017
DOI: 10.1097/md.0000000000006635
|View full text |Cite
|
Sign up to set email alerts
|

Does long-term efficacy differ between infliximab and adalimumab after 1 year of continuous administration?

Abstract: Although biologics are important inflammatory bowel disease therapies, loss of response (LOR) remains problematic. We evaluated LOR to biologics in our Crohn disease (CD) patients receiving biologics. Of 137 biologic-treated CD patients, 68 continuously receiving the same biologic type for at least 1 year were divided into 2 groups: infliximab (IFX) (n = 39) and adalimumab (ADA) (n = 29). Clinical courses were compared at biologic introduction and at 1 year. Both groups were retrospectively analyzed for LOR at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 15 publications
4
8
0
Order By: Relevance
“…In a large retrospective and prospective multicenter study for identify- was identified as a predictive factor for LOR. 26 Similar results were observed in our study; patients with younger age at CD onset were more likely to suffer from LOR after initiating IFX therapy.…”
Section: Discussionsupporting
confidence: 91%
“…In a large retrospective and prospective multicenter study for identify- was identified as a predictive factor for LOR. 26 Similar results were observed in our study; patients with younger age at CD onset were more likely to suffer from LOR after initiating IFX therapy.…”
Section: Discussionsupporting
confidence: 91%
“…The short‐term efficacy, including achievement of steroid‐free remission, and the continuation of the first anti‐TNF agent were similar between the patients treated with IFX first and those treated with ADA first, and these results were consistent with those reported in previous studies . The similarity of our patient characteristics and short‐term outcomes with those in previous studies suggests a high level of confidence in the quality of our long‐term outcome analysis, which is the highlight of the current study.…”
Section: Discussionsupporting
confidence: 89%
“…No head‐to‐head comparisons have been performed regarding which agent, IFX or ADA, should be administered first for biologic‐naïve CD patients. Therefore, several retrospective and a few prospective studies have compared the rates of clinical or steroid‐free remission, surgery, loss of response (LOR), and adverse events between patients who received IFX first and those who received ADA first . However, most of these previous reports evaluated relatively short‐term outcomes only and discontinued observation of patient clinical courses at the first episode of LOR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, higher therapeutic goals beyond clinical remission alone, such as mucosal healing and deep remission, have also been pursued. However, some problems associated with the use of anti-TNFα drugs have been identified, such as the onset of secondary failure, in which the drugs become progressively less effective with time, 1 3 and the occurrence of paradoxical skin reactions, eg, psoriatic manifestations. 4 , 5 …”
Section: Introductionmentioning
confidence: 99%